The Effect of Body Shaming on the Existence of Generation Z Confidence - Natasya Dwina Sukoco; Daru Purnomo; Suryo Sakti Hadiwijoyo (Budapest International Research and Critics University, 2022)
Body shaming is the treatment of a person in giving negative comments to a person's physical condition (body or appearance), whether consciously or not. Body shaming affects the level of self-confidence of a person, both male and female, from the age of 13 years to the age of 36 years. This means that body shaming affects both generation Z and the millennial generation. The purpose of this study is to describe the forms of body shaming experienced by Generation Z adolescents in Salatiga City and explain the effect of body shaming on the existence of self-confidence of Generation Z adolescents in Salatiga City. This study uses quantitative methods with the type of explanatory research. The results of this study indicate a strong correlation coefficient of 0.715, which means that there is a correlation between the body shaming variable and the self-confidence variable of generation Z teenagers in Salatiga City. The effect of body shaming on the intensity of self-confidence of Generation Z is 51.2%, while the remaining 48.8% is influenced by other factors not examined by researchers. The F test shows a probability value of 0.000 <0.05, which means that H1 is accepted and H0 is rejected. From this study obtained a significance value of 0.000, it can be concluded that body shaming has an influence on the existence of self-confidence of generation Z teenagers in Salatiga City.